Interaction of EU Financial Interest and Legal Principles in EU Criminal Law - Gruodytė, Edita; Milčiuvienė, Saulė; Volungevičienė, Rasa; Molienė, Reda (Teisė, 2022)
This article examines the intersection differing the supremacy of law, the effectiveness of the protection of the financial interests of the European Union, and the principles of legality the same as predictability of the law in EU criminal law. The authors analyze the jurisprudence of the Court of Justice, assessing cases where the principle of the supremacy of EU law is applied to ensure the effective protection of the Union’s financial interests and where the ECJ imposes mandatory exceptions to this principle for national courts. In order to strike a balance between the principles of effectiveness and legal predictability, different liability conditions are assessed for a natural person and a Member State that fails to fulfill its obligation to protect the EU’s financial interests.
Keywords: European Union financial interests; European Union criminal law; general principles of law; operation of directives; protection of fundamental rights